Uji Aktivitas Antibakteri Ekstrak Daun Pepaya Jepang (Cnidoscolus aconitifolius) Dengan Metode Difusi Agar - Maria Fatmadewi Imawati; Septya Dwi Hartanti; Levi Puradewa (Jurnal Ventilator, 2023)
Japanese papaya leaves (Cnidoscolus aconitifolius) contain active compounds such as flavonoids, tannins, saponins, alkaloids and terpenoids which have the potential to have antibacterial activity. The aim of this research is to determine the antibacterial activity of Japanese papaya leaves against Staphylococcus aureus bacteria. Extraction of Japanese papaya leaves has been carried out using the maceration method and 96% ethanol solvent. The antibacterial activity test used the agar diffusion method using a cylindrical plate. Sterile distilled water was used as a negative control while as a positive control the antibiotic ciprofloxacin was used. The concentrations of Japanese papaya leaf ethanol extract used in testing were 10%, 20%, and 30%. The research results showed that Japanese papaya leaf ethanol extract with a concentration of 30% had the widest inhibition zone diameter, namely 17.296 mm. Meanwhile, at a concentration of 20%, the average inhibitory zone diameter was 15,222 mm, and at a concentration of 10%, the average inhibitory zone diameter was 13,018 mm. These three concentrations were included in the strong category based on Greenwood classification.